IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Febry Angellyca Sulistianingrum; Tarpan Suparman; Aang Solahudin Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
One learning approach that emphasizes the scientific process in understanding basic science and science concepts in elementary schools is the scientific approach. This research will analyze how the scientific approach is applied in science and science learning in elementary schools, with a focus on the application of processes such as observation, asking questions, experiments, data analysis, and communicating the results. Qualitative descriptive research is used to collect data through observation, interviews and documentation. The research results show that the scientific method can help students become more engaged in lessons, improve their ability to think critically, and increase their understanding of concepts. However, its implementation raises several obstacles; Laboratory facilities are limited and teacher resources must be increased. This research shows that teachers need additional training, as well as improved facilities and supporting equipment.